BUILDING RESILIENT AND EMPOWERED COMMUNITIES THROUGH HOMESTAY TOURISM: A SUSTAINABILITY CASE FROM PERAK, MALAYSIA - Ismail, Nur Hamizan; Abd Wafi, Anisah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2026)
There was limited integration between homestay tourism and TVET, particularly in Perak, where cultural heritage, natural attractions, and community participation shape the tourism landscape. Besides, there were insufficient studies on income generation; homestay initiatives offer opportunities for capacity building, skill enhancement, and the empowerment of local communities to engage more effectively in the tourism economy. This study examines the role of homestay tourism in fostering community-based products in Perak by integrating Technical and Vocational Education and Training (TVET). Adopting a qualitative approach, data were collected through in-depth interviews and field observations with eight homestay operators and community leaders in selected villages. Findings indicate that homestay participation nurtures hospitality, entrepreneurial, and interpersonal skills, while simultaneously strengthening community resilience and sustainable tourism practices. However, the study also identifies challenges, including limited access to formal training, resource disparities, and weak policy coordination and institutional support for homestay operators. It is argued that integrating structured training modules, such as knowledge transfer programs, into community-based tourism initiatives can enhance local capacity, improve service quality, and support the long-term sustainability of homestay tourism. The paper concludes with policy recommendations for aligning Malaysia’s tourism development strategies with its national TVET agenda to advance inclusive and sustainable rural empowerment.